2021
DOI: 10.1088/1361-6528/abf87c
|View full text |Cite
|
Sign up to set email alerts
|

Photo generated charge transport studies of defects-induced shuttlecock-shaped ZnO/Ag hybrid nanostructures

Abstract: We report the stimulating effects of interfacial charge transfer process between spherical Ag nanoparticles and shuttlecock-shaped ZnO nanostructures observed by UV−visible spectroscopy and x-ray absorption spectroscopy. In specific, ZnO nanorods and shuttlecock-shaped ZnO/Ag nanostructures were developed using a simple chemical colloidal method and characterized for structural variations using XRD. The observed red shift in plasmonic peak and the increase in Urbach energy signify interfacial interactions and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 68 publications
(77 reference statements)
0
3
0
Order By: Relevance
“…The absorbance spectra obtained was used to calculate the degradation efficiency of the photocatalyst for the dye solution using the formula:where C 0 is the initial dye concentration and C t is the concentration of the dye in the supernatant solution after time t . 28,29 A schematic of the homemade photocatalytic setup used in the study is shown in Fig. 1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The absorbance spectra obtained was used to calculate the degradation efficiency of the photocatalyst for the dye solution using the formula:where C 0 is the initial dye concentration and C t is the concentration of the dye in the supernatant solution after time t . 28,29 A schematic of the homemade photocatalytic setup used in the study is shown in Fig. 1.…”
Section: Methodsmentioning
confidence: 99%
“…where C 0 is the initial dye concentration and C t is the concentration of the dye in the supernatant solution after time t. 28,29 A schematic of the homemade photocatalytic setup used in the study is shown in Fig. 1.…”
Section: Photocatalytic Degradation Of Rh-b Dyementioning
confidence: 99%
See 1 more Smart Citation